2021
DOI: 10.12998/wjcc.v9.i26.7876
|View full text |Cite
|
Sign up to set email alerts
|

Congenital disorder of glycosylation caused by mutation of ATP6AP1 gene (c.1036G>A) in a Chinese infant: A case report

Abstract: BACKGROUND The ATP6AP1 gene coding for the accessory protein Ac45 of the vacuolar-type adenosine triphosphatases (V-ATPase) is located on chromosome Xq28. Defects in certain subunits or accessory subunits of the V-ATPase can lead to congenital disorders of glycosylation (CDG). CDG is a group of metabolic disorders in which defective protein and lipid glycosylation processes affect multiple tissues and organs. Therefore, the clinical presentation of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Among 20 individuals (Jansen et al 2016;Dimitrov et al 2018;Witters et al 2018;Gumm et al 2020;Ondruskova et al 2020;Tvina et al 2020;Yang et al 2021) summarized in Table 2 (18 reported in the literature and two from the current study), 17 showed hepatomegaly/liver failure/cirrhosis, 16 showed recurrent infection, 13 showed splenomegaly, 8 showed neurological symptoms, 6 showed cutis laxa, 5 were reported to have cardiac abnormalities or bilateral inguinal hernias, and 3 had a congenital diaphragmatic hernia. None of the individuals reported in the literature with ATP6AP1-CDG have been reported with ventriculomegaly, umbilical hernia, pectus carinatum, micropenis, or hypospadias, which we found in the probands in this study.…”
Section: Literature and Database Reviewmentioning
confidence: 80%
“…Among 20 individuals (Jansen et al 2016;Dimitrov et al 2018;Witters et al 2018;Gumm et al 2020;Ondruskova et al 2020;Tvina et al 2020;Yang et al 2021) summarized in Table 2 (18 reported in the literature and two from the current study), 17 showed hepatomegaly/liver failure/cirrhosis, 16 showed recurrent infection, 13 showed splenomegaly, 8 showed neurological symptoms, 6 showed cutis laxa, 5 were reported to have cardiac abnormalities or bilateral inguinal hernias, and 3 had a congenital diaphragmatic hernia. None of the individuals reported in the literature with ATP6AP1-CDG have been reported with ventriculomegaly, umbilical hernia, pectus carinatum, micropenis, or hypospadias, which we found in the probands in this study.…”
Section: Literature and Database Reviewmentioning
confidence: 80%
“…9 Many patients have laboratory abnormalities, including low serum copper and/or ceruloplasmin and hypercholesterolemia. 1,[8][9][10][11][12][13] Neurological manifestations of ATP6AP1-CDG vary among patients and include epilepsy, sensorineural hearing loss (SNHL), intellectual disability, and developmental delay. 1,9,13 Here we report 11 new patients with ATP6AP1-CDG from eight different families and four novel ATP6AP1 variants and provide clinical manifestation updates and glycomic results on a previously reported patient.…”
Section: Introductionmentioning
confidence: 99%
“…ATP6AP1‐CDG was first identified in 2016 in eleven patients from six families 1 . Subsequently, eight more ATP6AP1‐CDG cases from another six families have been reported in the literature 8–13. Affected patients frequently exhibit coagulopathy, elevated liver enzymes, cholestatic jaundice, low immunoglobulins, recurrent infections, and reduced response to vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations